2014
DOI: 10.2319/101013-748.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pharyngeal airway volume among different vertical skeletal patterns: A cone-beam computed tomography study

Abstract: Objective: To test the null hypothesis that there are no significant differences in pharyngeal airway volumes among adult patients with different vertical skeletal patterns and a clinically normal sagittal skeletal pattern using cone-beam computed tomography (CBCT). Material and Methods: The study sample consisted of 100 adult patients (45 men and 55 women; mean age 5 24.0 6 5.3 years) with a normal sagittal skeletal pattern divided into three groups according to the vertical skeletal patterns: high angle (32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 21 publications
3
42
0
2
Order By: Relevance
“…Because CBCT has been shown to be a reliable method for assessing dehiscences and fenestrations, we decided to use these images in cleft patients, a technique that has not been reported previously. Consistent with previous studies 4,5,[18][19][20][21][22][23][24] showing the high reliability of CBCT for 2-D and 3-D measurements, agreement was 100% for the detection of dehiscences and fenestrations. Although Sun et al 12 reported that this method might overestimate the actual measurements, the technique was reported to have the highest sensitivity and diagnostic accuracy for detecting various periodontal defects.…”
Section: Discussionsupporting
confidence: 79%
“…Because CBCT has been shown to be a reliable method for assessing dehiscences and fenestrations, we decided to use these images in cleft patients, a technique that has not been reported previously. Consistent with previous studies 4,5,[18][19][20][21][22][23][24] showing the high reliability of CBCT for 2-D and 3-D measurements, agreement was 100% for the detection of dehiscences and fenestrations. Although Sun et al 12 reported that this method might overestimate the actual measurements, the technique was reported to have the highest sensitivity and diagnostic accuracy for detecting various periodontal defects.…”
Section: Discussionsupporting
confidence: 79%
“…Current correlation analysis showed an inverse correlation between NA and the mandibular plane angle in the RH-HD group, consistent with Freitas et al, 23 who found that vertical growth patterns influenced upper airway dimensions. Confirming this point, Celikoglu et al 24 found that the nasopharyngeal and oropharyngeal airway volume were significantly higher in the low-and normal-angle groups than in the high-angle group. Ucar and Uysal 16 also reported a decrease in nasopharyngeal airway space from low-angle to normal-to high-angle cases.…”
Section: Discussionmentioning
confidence: 50%
“…Oktay and Ulukaya 10 also reported that the changes in the pharyngeal measurements of patients aged 11.7 years for a duration of 8 months were at a negligible level. In addition, future prospective studies using cone-beam computed tomography images with larger study samples could provide accurate findings and provide an opportunity for clinicians to compare their findings with ours because those images were reported to have several advantages [28][29][30][31] when compared with the conventional cephalometric films. Thus, the findings of the present prospective clinical study should be assessed within the limitations of the two-dimensional radiography design used for the assessment of the pharyngeal airway.…”
Section: Discussionmentioning
confidence: 99%